Why Are Patients With COVID-19 at Risk for Drug-Drug Interactions?. Issue 6 (November 2020) - PRESKORN, SHELDON H.; QUADRI, SYEDA
Abstract : The goal of this column is to provide information to health care professionals about drug-drug interactions (DDIs) and why DDIs are important to consider in those at serious risk of illness with Coronavirus Disease 2019 (COVID-19). Important considerations discussed in this column include the frequency and complexity of multiple medication use, particularly important for the older patient who often has multiple comorbid illnesses. The column covers the following issues: (1) Why patients at high risk for serious illness from COVID-19 are also at high risk for DDIs. (2) Application of results of pharmacoepidemiological studies to the population at risk for serious COVID-19 illness. (3) Mechanisms underlying DDIs, frequency and potential complexity of DDIs, and how DDIs can present clinically. (4) Methods for preventing or mitigating DDIs. (5) An introduction to the University of Liverpool drug interaction checker as a tool to reduce the risk of adverse DDIs while treating patients for COVID-19. Commentary is also provided on issues related to specific psychiatric and nonpsychiatric medications a patient may be taking. A subsequent column will focus on DDIs between psychiatric medications and emerging COVID-19 treatments, as a detailed discussion of that topic is beyond the scope of this column.